P248 Risk of exacerbation and pneumonia with single inhaler triple versus dual therapy in IMPACT. (December 2018) - Dransfield, M; Crim, C; Criner, G; Halpin, DMG; Han, MK; Jones, CE; Kilbride, S; Lange, P; Lipson, DA; Lomas, DA; Martinez, F; Singh, D; et al.
Abstract : Background: To determine overall benefit-risk, we examined the effect of single inhaler fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) versus UMEC/VI and FF/VI on the composite outcome of acute exacerbation of COPD or pneumonia in the IMPACT study (NCT02164513, CTT116855), a 52 week, randomized, multicentre study in patients with symptomatic COPD and a history of exacerbations Methods: We defined two composite outcomes: time to first moderate (required antibiotics and/or oral/systemic corticosteroids)/severe (required hospitalisation) exacerbation or pneumonia; and time to first severe exacerbation/hospitalised pneumonia. Analyses were based on a proportional hazards model. Results: Moderate/severe exacerbations occurred in 47% of patients randomized to FF/UMEC/VI, 49% in those randomized to FF/VI and 50% in those randomized to UMEC/VI. Pneumonias occurred in 8%, 7%, and 5% of patients in these groups, respectively. FF/UMEC/VI reduced the risk of first moderate/severe exacerbation or pneumonia vs FF/VI by 13.2% (95%CI 7.8%–18.3%; p<0.001) and vs UMEC/VI by 13.1% (95%CI 6.3%–19.3%; p<0.001) as determined by a time to first analysis. There was no difference in the risk of a moderate/severe exacerbation or pneumonia between FF/VI and UMEC/VI. FF/UMEC/VI reduced the risk of a severe exacerbation or hospitalized pneumonia vs UMEC/VI by 16.9% (95%CI 4.2%–27.8%, p=0.011) as determined by a time to first analysis. There was no statistically significant difference in the risk of a severe exacerbation or hospitalized pneumonia between FF/UMEC/VI and FF/VI or between FF/VI and UMEC/VI. Conclusion: These composite exacerbation/pneumonia outcomes support a favourable benefit-risk profile of once-daily FF/UMEC/VI compared with FF/VI and UMEC/VI in patients with moderate to severe COPD and a history of exacerbations. Funding: GSK (CTT116855); This ENCORE abstract will be presented as a poster at the 2018 European Respiratory Society Meeting in September.